Households' Livelihood Vulnerability to Climate Change and Climate Variability: A Case Study of the Coastal Zone, The Gambia - Joshua Amuzu; Amos T. Kabo- Bah; Bubu Pateh Jallow; Sidat Yaffa (Journal of Environment and Earth Science, 2018)
Climate change and its variability are negatively influencing climate-dependent activities such as agriculture and fishing in Africa, of which The Gambia is no exception. Households are vulnerable to its impacts. With the impacts of climate change and its variability in The Gambia, livelihoods of people will be negatively affected. There is the need to know which regions are more vulnerable than others are so livelihood improvement actions can be taken in areas they are needed the most in the wake of present and future climate change impacts, thus, the objective of this study. This will aid in eluding maladaptation and waste of limited developmental resources for climate change adaptation. The results of the study will also assist the Government and other development partners in making decisions that are more informed as to areas where and the kind of assistance needed between the districts in the coastal zone of The Gambia. The study employed the Livelihood Vulnerability Index (LVI) in the estimation of household vulnerability to Climate Change (CC) and its variability based on their: Socio-Demographic Profile; Livelihood strategies; Social Networks; Health; Water; Natural disasters and Climate Variability and; Knowledge and Skills. This approach is divided into the Intergovernmental Panel on Climate Change (IPCC) three main components of vulnerability, namely: Exposure; Sensitivity and; Adaptive Capacity. The primary data used is based on a survey of 355 household heads in agriculture or fishing activities in the coastal zone of The Gambia, while the secondary data used was on rainfall and temperature. Microsoft Office Excel 2016 was the software employed in estimating the livelihood vulnerability index, developing the vulnerability spider (radar) chart and the vulnerability triangle in this study. The findings of the study reveal households in Kombo South may be more vulnerable to climate change and its variability than Lower Niumi districts in the study area. The LVI revealed Kombo South district may be more vulnerable to: Health; Food and; Knowledge and Skills while Lower Niumi district is more vulnerable to: Socio-Demographic Profile; Livelihood Strategies; Social Networks; Water and; Natural Disasters and Climate Variability. The overall LVI-IPCC main components of vulnerability reveals households in Kombo South may be more vulnerable than households in Lower Niumi district in the coastal zone of The Gambia.
Keywords: 330; Vulnerability; The Gambia; Climate Variability; Livelihood Vulnerability Index; Climate Change; Households; Farmers; Coastal Zone